RELIGIOUS DRAMA CONTROVERSY: The Impact of Bidaah on Islamic Pedagogy and Media Literacy - Hanifansyah, Nur; Arifin, Ahmad; Zulpina, Zulpina; Mahmudah, Menik; Syaheed, Syarif Muhammad (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2025)
This study explores audience reception of the Malaysian drama Bidaah through the perspectives of pedagogy and media literacy, focusing on how cinematic depictions of religious manipulation shape perceptions in Malaysia and Indonesia. Using a descriptive-exploratory qualitative method supported by quantitative data, the research analyzed social media discourse, surveyed 100 respondents, and interviewed 20 Islamic educators from both countries. Findings show divided responses: Indonesian audiences tended to value the film’s artistic critique of spiritual abuse, while most educators expressed concern about its potential to distort views of Islamic leadership. Thematic analysis highlights issues of charismatic dominance, symbolic language, and emotional religious rhetoric in media. The study argues that educators should move beyond binary judgments and instead foster critical, ethical media engagement. Bidaah thus becomes not only a cinematic controversy but also a pedagogical opportunity to nurture discernment, compassion, and media-literate faith.